2012
DOI: 10.1371/journal.pone.0040128
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal CA1 Transcriptional Profile of Sleep Deprivation: Relation to Aging and Stress

Abstract: Background Many aging changes seem similar to those elicited by sleep-deprivation and psychosocial stress. Further, sleep architecture changes with age suggest an age-related loss of sleep. Here, we hypothesized that sleep deprivation in young subjects would elicit both stress and aging-like transcriptional responses. Methodology/Principal Findings F344 rats were divided into control and sleep deprivation groups. Body weight, adrenal weight, corticosterone level and hip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 81 publications
3
25
0
1
Order By: Relevance
“…These widespread changes in hippocampal gene expression were reversed with 2.5 h of recovery sleep following sleep deprivation . Longer periods of sleep deprivation have also been examined with regard to gene expression in the hippocampus using microarray analysis to explore the relationship between age, stress, depression, and sleep disruption (Conti et al 2007;Porter et al 2012). In these studies, selective changes in genes related to presynaptic machinery and synaptic plasticity were identified.…”
Section: Gene Expression As a Results Of Sleep Deprivationmentioning
confidence: 99%
“…These widespread changes in hippocampal gene expression were reversed with 2.5 h of recovery sleep following sleep deprivation . Longer periods of sleep deprivation have also been examined with regard to gene expression in the hippocampus using microarray analysis to explore the relationship between age, stress, depression, and sleep disruption (Conti et al 2007;Porter et al 2012). In these studies, selective changes in genes related to presynaptic machinery and synaptic plasticity were identified.…”
Section: Gene Expression As a Results Of Sleep Deprivationmentioning
confidence: 99%
“…These treatments were used to mimic stress effects and several studies reported the effects of the acute and chronic stresses modified differently the hippocampus transcriptome (Li et al, 2013; Stankiewicz et al, 2015). Furthermore, the nature of the stressor is also crucial (Porter et al, 2012; Li et al, 2013; Suri et al, 2014; Stankiewicz et al, 2015). Similarly to stress, modifications of living conditions, as well as long-term mild or intense exercise, can modulate the hippocampus transcriptome (Inoue et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reports sleep deprivation disrupts hippocampal function and synaptic plasticity, a neural correlate of memory (Prince et al, 2014). It is well-known that sleep deprivation impairs memory, and hippocampus-dependent memory consolidation is particularly sensitive to sleep loss (Porter et al, 2012). The consolidation of memories includes synaptic consolidation and systems consolidation, both of which can be regulated by sleep deprivation (Havekes and Abel, 2017).…”
Section: Introductionmentioning
confidence: 99%